Il Geoportale della Provincia di Treviso - Gnocato, Margherita; Cauduro, Luca; Piatto, Michele (GEOmedia, 2010)
Treviso province geoportal The Treviso province geoportal, one of the winner of the 2009 contest organized by AMFM GIS Italia, is a referring, exchange and data dissemination tool designed to operate within a unique regulatory directive: INSPIRE. All these functionalities work in a Open Source environment that provided a significant save of money and an efficient data publishing and integration with the GIS basic functionalities.